Resistência de biofilmes formados por micobactérias de crescimento rápido frente a antimicrobianos - Flores, Vanessa da Costa (2018)
Rapidly growing mycobacteria (RGM) are opportunistic pathogens that produce diseases in a variety of clinical settings. The environmental nature of RGM and their ability to assemble biofilms on different surfaces play a key role in their pathogenesis.Biofilms constitute a protected mode of growth that allows microorganisms to survival in hostile environments, being their physiology and behavior significantly different from their planktonic counterparts. Biofilms pose a serious problem for public health because of the increased resistance of biofilm-associated organisms to antimicrobial agents and the potential for these organisms to cause infections. When in biofilms form, mycobacteria are highly resistant to antibacterial treatments. Nanoparticle-based therapies are viable approaches when it comes to treating biofilm associated infections due to chemical and physical properties of such nanostructured systems, granted by a high superficial area to volume ratio. Bearing in mind the importance of comprehending all factors that cause mycobacteriosis treatments to fail, e.g. biofilm formation, the main objective of this study is to evaluate resistance to antimicrobials in RGM biofilms. The tested antimicrobials were amikacin, ciprofloxacin, clarithromycin, doxycycline, imipenem and sulfamethoxazole, which are ordinarily employed in the treatment of mycobacteriosis. For each drug, evaluation was done according to the susceptibility of the pathogen, the ability to inhibit biofilm formation and the resistance of biofilms to antimicrobial activity. Furthermore, due to the broad use of clarithromycin in therapeutic schemes against micobacterial infections, clarithromycin nanocapsules (NC-CLA) were developed and employed. Its antibiofilm properties were evaluated, as were those of the other above stated antimicrobials. Results showed that although the tested antimicrobials are used as an alternative therapy for RGM, Mycobacterium abscessus presented to be resistant to clarithromycin and Mycobacterium massiliense showed a resistant profile to clarithromycin and sulfamethoxazole. Furthermore, the inhibition of biofilm formation and its destruction have not been fully met. The nanoencapsuled clarithromycin form showed higher capability in inhibiting biofilm formation and in microbial pellicle destruction than free clarithromycin, that is, in all tested concentrations and for all three RGM strains that were utilized in the essay. Thus, actions that aim to optimize antimicrobial permeability in the exopolimeric matrix emerge as important prevention strategies against formation of biofilm and in its combat.